Nocturnal Coleoptera and Hemiptera Diversity at Giam Siak Kecil Bukit Batu Biosphere Reserve Indonesia - Hasni Ruslan; Imran S. L. Tobing (Jurnal Biodjati, 2021)
Giam Siak Kecil Bukit Batu is a biosphere reserve which one of its functions is as a habitat for wildlife. However, biodiversity data in the Giam Siak Kecil Bukit Batu Biosphere Reserve (GSKBB-BR) is still very minimal, including insects (Coleoptera and Hemiptera). This research was conducted to determine the diversity of Coleoptera and Hemiptera in the GSKBB Biosphere Reserve, Riau, Indonesia. The research was carried out using an exploratory method using "lights trap". The results of the study found 30 species, from 11 families of the order Coleoptera (23 species) and Hemiptera (7 species) in the GSKBB-BR. The diversity index of Coleoptera and Hemiptera at the observation site was moderate (H = 2.73), with a high evenness index (0.80). Scarabaeidae (order Coleoptera) is the family with the highest number of species found (8 species), while the most abundant species were Tibicen linnei and Pomponia fusca (Cicadidae/Hemiptera). Based on their functional roles, Coleoptera and Hemiptera with the highest number are herbivores (17 species), followed by predators (7 species) and decomposers (3 species). The range of values for temperature and humidity at the research site are in normal conditions. The GSKBB-BR area is an important remaining habitat for wildlife in Riau, including various types of insects (Coleoptera and Hemiptera); whose potential still needs to be revealed, and must be managed properly.